Great combat handguns a guide to using, collecting, and training with handguns - Thompson, Leroy; Smeets, Rene (Blandford Press ; Sterling Publishing Co, Inc, 1987)
Over 50 of the best personal handguns available worldwide are selected, assessed and tested. As well as full technical data and handling characteristics each handgun has photographic and line artwork illustrations - chapters also include advice on choice of ammunition, the various carrying methods, choosing a weapon for specific uses as well as the expanded firearm directory.